GOOGLE SITE Y SU CONTRIBUCIÓN EN LA INNOVACIÓN DIGITAL DE EMPRENDIMIENTO EN LOS ESTUDIANTES DE LA CARRERA DE PEDAGOGÍA DE LAS CIENCIAS EXPERIMENTALES INFORMÁTICA, PERIODO OCTUBRE 2023 - MARZO 2024. - PAZMIÑO MASTIAN EHILYN JAZMÍN (2024)
The purpose of this project is the design a website on the Google Site platform and its contribution to the digital innovation of ventures of the students of the Experimental Sciences Pedagogy – Computer Science career in the academic period October 2023 - March 2024 whose objectives are to determine and identify the specific functionalities of this tool and Explain your current innovative status and design a website. In this project, various types of research were used, including exploratory, descriptive, and applicative, which allowed different aspects of the topic in question to be addressed from various perspectives. This quantitative research design facilitated a deep and holistic understanding of the phenomenon studied, thus allowing a more complete and precise view of the results obtained. On the other hand, the total population is 436 divided into 295 women and 141 men from the entire career, with a sample of 226 students. Finally, the contribution of Google Site has proven to be an important step towards building a more innovative, collaborative educational environment oriented towards the development of digital and entrepreneurial skills in students.